Preparation method of super-hydrophobic coating and shape memory composite base cloth and umbrella of super-hydrophobic coating and shape memory composite base cloth

By combining atmospheric plasma jet and fluorosilane coating with nanometal oxide deposition and double-layer jacquard weaving, the pollution and adhesion problems in superhydrophobic surface preparation are solved, and the preparation of superhydrophobic and shape memory composite substrates is realized, which is suitable for high-end rain gear.

CN120536873AActive Publication Date: 2025-08-26ZHEJIANG TIANHE NEW MATERIALS TECHNOLOGY CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202510763056.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-09
Publication Date
2025-08-26
Estimated Expiration
2045-06-09

AI Technical Summary

Technical Problem

The prior art has problems such as chemical waste liquid pollution, high cost, easy damage to the fiber structure of the base cloth and insufficient adhesion when preparing the superhydrophobic surface, and traditional methods are difficult to achieve efficient hydrophobicity and shape memory functions under normal pressure.

Method used

The surface of the base cloth is activated under normal temperature and pressure by using an atmospheric pressure plasma jet device. Combined with the preparation method of fluorosilane coating and shape memory composite substrate cloth, the superhydrophobic coating is formed by deposition of nanometal oxide layer and double-layer jacquard weaving, and permanent crease memory is formed by hot pressing.

Benefits of technology

It has achieved a significant improvement in the superhydrophobicity of the base cloth surface, with a rolling angle of ≤2°, a 35% reduction in folding resistance, and has self-cleaning and shape memory functions, which is suitable for high-end rain gear.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120536873A_ABST
    Figure CN120536873A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a super-hydrophobic coating and shape memory composite base cloth and an umbrella thereof, and belongs to the technical field of paints.The preparation method comprises the following steps that S1, base cloth pretreatment is conducted, S2, surface activation is conducted on the base cloth through an atmospheric pressure plasma jet device; s3, evaporation at normal temperature and normal pressure: placing the base cloth in a closed container, and suspending and fixing the base cloth; a fluorine-containing silane surface modifier FAS-17 is injected into the closed container; and standing at room temperature to isolate the closed container from external air and reach saturated vapor pressure, so as to obtain a colorless and low-surface-energy super-hydrophobic coating on the surface of the base cloth, thereby forming the composite base cloth. According to the scheme, on the basis of a physical-chemical synergistic mechanism, a micro-nano rough groove structure is constructed through plasma deposition, and chemical hydrophobic modification is realized in combination with the fluorosilane coating, so that the contact angle of the composite base cloth reaches 152 + / -2 degrees, the rolling angle is less than or equal to 2 degrees, and the composite base cloth presents stable super-hydrophobicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a preparation method of a super-hydrophobic coating and a shape memory composite base fabric and an umbrella thereof. Background Art

[0002] Setting a super-hydrophobic surface on the umbrella surface can prevent water from adhering to it, and at the same time has good self-cleaning ability to keep the surface clean. Traditional super-hydrophobic surface preparation technologies include wet chemical etching, electrochemical coating, sol-gel method, photolithography, sputtering, phase separation, etc. Wet chemical etching or electrochemical coating requires the use of strong acid / strong base reagents, which produces chemical waste liquid that pollutes the environment. At the same time, the process temperature is high, which can easily damage the fiber structure of base fabrics such as polyester and nylon. The sol-gel method requires high-temperature heat treatment to form an anatase-type hydrophobic structure. Sputtering or photolithography relies on vacuum equipment and is too expensive.

[0003] Atmospheric pressure plasma jet (APPJ) is a non-equilibrium low-temperature (50–90°C) plasma jet generated in an open environment at atmospheric pressure. It forms a highly active particle flow through gas discharge (such as dielectric barrier discharge and nanosecond pulse discharge), avoiding thermal damage and vacuum confinement.

[0004] Chinese patent publication number CN113231273A discloses a method for depositing a functional coating using atmospheric pressure low-temperature plasma, which deposits and sprays a functional coating on the surface of a rubber material, introduces polar groups, and improves the surface hydrophilicity.

[0005] When applying atmospheric pressure plasma jet technology to base fabrics, it is necessary to consider how to increase the hydrophobicity of the base fabric surface rather than enhance the surface hydrophilicity, and to increase the adhesion between the coating and the base fabric. Summary of the Invention

[0006] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a method for preparing a super-hydrophobic coating.

[0007] Another object of the present invention is to provide a method for preparing a shape memory composite base fabric.

[0008] Another object of the present invention is to provide an umbrella using the composite base fabric.

[0009] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions.

[0010] A method for preparing a super-hydrophobic coating comprises the following steps: Step S1, base fabric pretreatment: Wash and dry the base fabric to remove surface contaminants; Step S2, using an atmospheric pressure plasma jet device to perform surface activation on the base fabric: The atmospheric pressure plasma jet device includes a cathode, a nozzle, a substrate, a gas system, and a DC power supply. The cathode is made of tungsten metal; the gas system consists of a working gas and a reactive gas, wherein the working gas is argon and the reactive gas is oxygen. The substrate is placed on the substrate, and the working gas and reactive gas are mixed and injected into the nozzle. A DC power supply is applied to ignite the plasma, and a blue glow discharge appears at the tip of the nozzle. The generated plasma jet scans the entire substrate area at a constant scanning rate, completing the surface activation of the substrate and depositing a nano-metal oxide layer on the upper surface of the substrate. Step S3, evaporation at room temperature and pressure: The base fabric is placed in a sealed container and fixed in suspension; the fluorine-containing silane surface modifier FAS-17 is injected into the sealed container; and the sealed container is allowed to stand at room temperature to isolate the sealed container from the outside air and reach saturated vapor pressure, thereby obtaining a colorless, low-surface-energy super-hydrophobic coating on the surface of the base fabric to form a composite base fabric.

[0011] Furthermore, in step S1, the base fabric is sequentially cleaned with acetone, isopropyl alcohol, and deionized water by ultrasonic cleaning for 4 to 6 minutes each; and then dried in an oven at 80° C. for 30 minutes.

[0012] Furthermore, in step S2, the nozzle is made of stainless steel, and a metal rod with a diameter of 1 mm and a length of 175 mm is placed at the center of a stainless steel nozzle with a diameter of 2 mm; the inner diameter of the nozzle is 2 mm, and the gap between the cathode and the nozzle is 0.5 mm; the distance between the nozzle and the substrate is fixed at 2 mm; the parameters of the DC power supply are 150 V and 1 A.

[0013] Furthermore, in step S3, the volume ratio of the fluorine-containing silane surface modifier to the sealed container is 0.012%.

[0014] A method for preparing a shape memory composite base fabric, comprising the following steps: Step S1, base fabric weaving: The warp yarn is made of polyamide 6 filament; the weft yarn is made of polypropylene monofilament and polyamide 6 low-elastic yarn mixed in a ratio of 1: (2-4); The base fabric adopts double-layer jacquard weaving, including surface layer and bottom layer; the surface layer is plain weave structure, with a warp density of 380 to 450 yarns per inch and a weft density of 300 to 380 yarns per inch; the bottom layer is honeycomb grid structure with a grid aperture of 0.5 to 1.0 mm; Step S2, calendering treatment: the hydrostatic pressure resistance value of the base fabric after calendering is ≥350mm water column; Step S3, compounding the hydrophobic coating, comprises: Step S301: pre-treatment of base fabric: Wash and dry the base fabric to remove surface contaminants; Step S302: Activate the surface of the base fabric using an atmospheric pressure plasma jet device. The atmospheric pressure plasma jet device includes a cathode, a nozzle, a substrate, a gas system, and a DC power supply. The cathode is made of tungsten metal; the gas system consists of a working gas and a reactive gas, wherein the working gas is argon and the reactive gas is oxygen. The substrate is placed on the substrate, and the working gas and reactive gas are mixed and injected into the nozzle. A DC power supply is applied to ignite the plasma, and a blue glow discharge appears at the tip of the nozzle. The generated plasma jet scans the entire substrate area at a constant scanning rate, completing the surface activation of the substrate and depositing a nano-metal oxide layer on the upper surface of the substrate. Step S303: evaporation at room temperature and pressure: The base fabric is placed in a sealed container and fixed in suspension; a fluorinated silane surface modifier FAS-17 is injected into the sealed container; and the container is allowed to stand at room temperature to isolate the sealed container from the outside air and reach saturated vapor pressure, thereby forming a colorless, low-surface-energy super-hydrophobic coating on the surface of the base fabric, thereby forming a composite base fabric; Step S4, hot pressing and shaping: After the composite base fabric is preheated by infrared to 100~120℃, the folding line is pre-pressed by a CNC crease pressing device with a pre-pressing pressure of 0.5~1.2MPa. It is then shaped by high-temperature hot air in the temperature range of 160~180℃ and the duration is 30~60s to form a permanent crease memory.

[0015] Further, in step S1, polyamide 6 filaments have a specification range of 40 to 80 deniers and a number of 48 to 144 monofilaments; Specifications of polypropylene monofilament: 20 to 60 denier, number of monofilament is 1; specifications of polyamide 6 low-elastic yarn: 30 to 70 denier, number of monofilament is 36 to 96.

[0016] Furthermore, in step S2, during the calendering treatment, the temperature is 150-170°C; the pressure is 13-17 MPa; the speed is 16-20 m / min; and the cooling method is air cooling.

[0017] Furthermore, in step S301, the base fabric is sequentially ultrasonically cleaned with acetone, isopropyl alcohol, and deionized water for 4 to 6 minutes each; and then dried in an oven at 80°C for 30 minutes; In step S302, the nozzle is made of stainless steel, and a metal rod with a diameter of 1 mm and a length of 175 mm is placed at the center of a stainless steel nozzle with a diameter of 2 mm. The inner diameter of the nozzle is 2 mm, and the gap between the cathode and the nozzle is 0.5 mm. The distance between the nozzle and the substrate is fixed at 2 mm. The parameters of the DC power supply are 150 V and 1 A. In step S303 , the volume ratio of the fluorine-containing silane surface modifier to the sealed container is 0.012%.

[0018] An umbrella, the base fabric of which adopts the super-hydrophobic coating described above, or the base fabric of which adopts the preparation method described above.

[0019] This solution has the following beneficial effects: Superhydrophobicity is significantly improved: Based on the physical-chemical synergistic mechanism, a micro-nano rough groove structure is constructed by plasma deposition, and combined with a fluorosilane coating to achieve chemical hydrophobic modification, so that the contact angle of the composite base fabric reaches 152°±2° and the rolling angle ≤2°, showing stable superhydrophobicity.

[0020] Shape memory and storage efficiency optimization: Adopting a double-layer heterogeneous weave design of polyamide 6 (PA6) and polypropylene (PP), the tension difference between the warp and weft yarns is used to form a directional crease line, reducing folding resistance by 35%. At the same time, through thermoplastic directional shaping, the PA6 molecular chains are prompted to arrange in an orderly manner along the crease direction, forming a permanent cross-linked network, completely eliminating the mechanical dependence of the umbrella on the metal frame for storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a schematic structural diagram of an atmospheric pressure plasma jet device; Figure 2 It is the SEM image of the base fabric surface; Figure 3 It is a dynamic image of water droplets on the treated base fabric surface. DETAILED DESCRIPTION

[0022] The present invention will be described in further detail below with reference to the accompanying drawings.

[0023] A method for preparing a super-hydrophobic coating comprises the following steps: Step S1: pretreatment of the base fabric.

[0024] Ultrasonic cleaning of the fabric was performed in acetone, isopropyl alcohol, and deionized water for 4-6 minutes each to remove surface oil. The fabric was then dried in an oven at 80°C for 30 minutes to ensure no residual moisture was present.

[0025] Ultrasonicate in acetone for 5 minutes to remove fat-soluble oils. Ultrasonicate in isopropyl alcohol for 5 minutes to dissolve polar residues. Ultrasonicate in deionized water for 5 minutes to rinse ionic impurities.

[0026] Step S2: Activate the surface of the base fabric using an atmospheric pressure plasma jet device.

[0027] Figure 1 is a schematic diagram of the structure of the atmospheric pressure plasma jet device; Figure 1As shown, the atmospheric pressure plasma jet device includes a cathode, a nozzle, a substrate, a gas system, and a DC power supply. The structure of the atmospheric pressure plasma jet device can be referred to Li Wenhao et al., "Design, Experimental and Simulation Research on Atmospheric Pressure Wide Radial Air Plasma Jet Device", Journal of Vacuum Science and Technology, 2019, 39(5): 420-427.

[0028] The cathode is made of tungsten metal doped with 2% thorium (WT20).

[0029] The nozzle is made of stainless steel, and a metal rod with a diameter of 1mm and a length of 175mm is placed in the center of a stainless steel nozzle with a diameter of 2mm to improve the stability of electron emission and extend the life of the electrode. To avoid uneven discharge, the cathode does not contact the nozzle wall (for example, the gap between the cathode and the inner wall of the nozzle is fixed at 0.5mm), and the diameter of the metal rod is slightly smaller than the inner diameter of the nozzle. The inner diameter of the nozzle is 2mm, and the gap between the cathode and the nozzle is 0.5mm to avoid uneven discharge and ensure the laminar flow characteristics of the jet. The distance between the nozzle and the substrate is fixed at 2mm, which is the optimal activation distance. The gas system consists of a working gas and a reactive gas. The working gas is argon at a flow rate of 15 SLM (standard liters per minute), and the reactive gas is oxygen at a flow rate of 40 SCCM (standard cubic centimeters per minute). Oxygen excites the surface to generate reactive oxygen atoms, enhancing surface hydroxylation.

[0030] The parameters of the DC power supply are 150V and 1A; The base fabric is placed on the substrate, and the working gas is mixed with the reaction gas and injected into the nozzle. A DC power supply of 150V and 1A is applied to ignite the plasma. A blue glow discharge appears at the tip of the nozzle, and the generated plasma jet scans the entire substrate area at a constant scanning rate of 4s / cm², completing the surface activation of the base fabric and depositing a nano-metal oxide layer on the upper surface of the base fabric.

[0031] Step S3: evaporation at room temperature and pressure.

[0032] For a superhydrophobic surface, the surface energy should be as low as possible. Reagents with perfluoroalkyl chains can reduce the surface energy.

[0033] The substrate was placed in a sealed container and suspended to avoid contact with the container walls. A fluorosilane surface modifier, FAS-17 (chemical name: 1H,1H,2H,2H-perfluorodecyltriethoxysilane), was then injected into the container. The volume ratio of the fluorosilane surface modifier to the sealed container was 0.012% (i.e., 120µL of fluorosilane surface modifier was used per 1L of the sealed container). The fluorosilane surfactant concentration was 97%, and the substrate was not in direct contact with the substrate. The container was then allowed to stand at room temperature for one hour to isolate it from the outside air and reach saturated vapor pressure. This resulted in a colorless, low-surface-energy, superhydrophobic coating on the substrate, forming a composite substrate.

[0034] The roll angle test is as follows: The sliding angle is a key parameter for characterizing the dynamic hydrophobicity of a superhydrophobic surface. The sliding angle test results of the base fabric before and after surface modification are as follows: Before modification: The rolling angle of the base fabric is about 35°, indicating that it only has basic waterproof performance and droplets are easily retained on the surface; After modification: After atmospheric pressure plasma jet (APPJ)-assisted nano-machining and silanization treatment, the roll angle is significantly reduced to about 2°.

[0035] Traditional coatings may exhibit good hydrophobicity (e.g., 130°), but exhibit a rolling angle exceeding 30°, indicating considerable adhesion to water droplets. In this approach, the fabric undergoes atmospheric pressure plasma jet (APPJ)-assisted nanofabrication and silanization, resulting in a dramatic decrease in the rolling angle, indicating enhanced hydrophobicity. The nanoparticles deposited on the fabric surface provide a larger surface area, enhancing its hydrophobicity and water repellency. The fabric surface becomes non-wetting, making it virtually impossible for water droplets to adhere to it. Instead, the droplets roll off spontaneously, achieving "zero-adhesion" anti-wetting properties.

[0036] Atmospheric pressure plasma jets were tested using different gases as follows: 1. Using pure argon as the gas system, the treated fabric exhibits super-hydrophilicity, with the lowest static surface contact angle dropping to 1.5°±0.5°; it returns to hydrophobicity after 48 hours. Therefore, a reactive gas is required in addition to the working gas.

[0037] 2. When argon containing 0.2% oxygen was used as the gas system and scanning was performed for more than 30 cycles, nanoparticles appeared on the surface of the base fabric. Figure 2 is the SEM picture of the base fabric surface; Figure 2 As shown, the surface of the base fabric is rough and a thin layer of nanoparticles is deposited.

[0038] The test of water droplets bouncing on the modified surface is as follows: Figure 3 It is a dynamic image of water droplets on the treated base fabric surface; Figure 3 The researchers demonstrated the dynamic behavior of a water droplet on a treated surface, recorded with a high-speed camera. The droplet was completely repelled by the treated surface in a remarkably short time, with an average time of 13.8 to 14.6 milliseconds. Furthermore, the researchers found that even after bouncing back and forth between the starting point and the surface more than ten times, the droplet still achieved a height of 44.4% to 51.8% of the first bounce at the end of its fifth bounce.

[0039] This scheme combines atmospheric pressure plasma jet deposition with evaporation to create a superhydrophobic surface with a rough, dual-layer topography. During the atmospheric pressure plasma jet deposition process, plasma-active tungsten ions first react with free radicals or oxygen in the turbulent air flow, and then deposit on the substrate surface as tungsten metal and partially oxidized tungsten. The deposited nanoparticles are primarily composed of tungsten trioxide, while the inner thin film contains partially oxidized tungsten oxide and metallic tungsten. The nanoparticles are initially deposited as metal and then gradually oxidize. Simultaneously, the tungsten trioxide prevents further oxidation within the nanoparticles. The deposited nanoparticles form a dual topography of a rough surface and an inner layer, trapping air to form an air cushion, which enhances superhydrophobicity. Evaporation causes the hydroxyl bonds on the substrate surface to self-assemble into fluoroalkylsilanes, forming metal-siloxane bonds. The coating is functionalized with terminal trifluoromethyl (-CF3) groups and long-chain -CF2- groups, reducing its surface energy to 15-23 mN / m.

[0040] A method for preparing a shape memory composite base fabric, comprising the following steps: Step S1, base fabric weaving: The warp yarn is made of polyamide 6 filament (PA6) with a specification range of 40 to 80 denier and 48 to 144 single filaments.

[0041] The weft yarn is made of a 1:2-4 ratio of polypropylene monofilament (PP) and polyamide 6 low-stretch yarn (PA6). The polypropylene monofilament specifications are 20 to 60 denier, with a single yarn count of 1; the polyamide 6 low-stretch yarn specifications are 30 to 70 denier, with a single yarn count of 36 to 96. The base fabric adopts double-layer jacquard weaving, including the surface layer and the bottom layer; The surface layer is a plain weave structure with a warp density of 380 to 450 threads per inch and a weft density of 300 to 380 threads per inch. The warp and weft yarns are tightly interwoven to form a high-density waterproof structure. The bottom layer is a honeycomb grid structure with a grid aperture of 0.5 to 1.0 mm, which provides deformation space, enhances the flexibility of the base fabric, and guides the folding direction.

[0042] Double-layer jacquard weaving is a textile process in which two sets of warp threads and two sets of weft threads are interwoven to form a double layer of front and back. It is described in Chinese patents with publication numbers CN101046025A, CN110144663A, CN207659593U and CN106884247A. Chinese patent publication number CN117005096A discloses a double-layer jacquard weaving process in which the front side of the fabric is a lower plate of the tissue structure and the back side of the fabric is an upper plate of the tissue structure (flat plain surface). This solution can be adopted in this solution.

[0043] Step S2, calendering treatment: A high-temperature and high-pressure calendering process is used to obtain a smooth and even base fabric. The hydrostatic pressure resistance value of the base fabric after calendering is ≥ 350 mm water column.

[0044] The temperature is 150~170℃, which is close to the melting point of polypropylene (165℃) but lower than the softening point of polyamide 6 (180℃), achieving selective melting of polypropylene fibers while protecting the polyamide 6 fiber skeleton structure from thermal damage.

[0045] The pressure is 13~17MPa. The high pressure drives the molten polypropylene to flow and fill the pores of the fabric, and simultaneously compacts the polyamide 6 fiber layer, significantly improving the density and mechanical strength of the base fabric.

[0046] The machine speed is 16~20 m / min to ensure uniform heat transfer (residence time ≈ 30s) to avoid local over-melting or insufficient solidification.

[0047] The cooling method is air cooling, which quickly solidifies the molten structure, inhibits the growth of polypropylene crystallinity, and retains the shape memory response potential of the base fabric.

[0048] Calendering treatment uses a three-step locking mechanism of PP melting, infiltration, and rapid cooling to set the shape. Melting: Polypropylene melts at a critical temperature; Infiltration: Molten polypropylene penetrates the fiber gaps under pressure; Rapid cooling: Air cooling rapidly solidifies to form physical crosslinks, locking the preset structure.

[0049] Step S3, compounding of the hydrophobic coating.

[0050] Step S301: pre-treatment of the base fabric.

[0051] Ultrasonic cleaning of the fabric was performed in acetone, isopropyl alcohol, and deionized water for 4-6 minutes each to remove surface oil. The fabric was then dried in an oven at 80°C for 30 minutes to ensure no residual moisture was present.

[0052] Step S302: Activate the surface of the base fabric using an atmospheric pressure plasma jet device.

[0053] The cathode is made of tungsten metal doped with 2% thorium (WT20).

[0054] The nozzle is made of stainless steel and is made into a metal rod with a diameter of 1mm and a length of 175mm. It is placed in the center of a stainless steel nozzle with a diameter of 2mm to improve the stability of electron emission and extend the life of the electrode. To avoid uneven discharge, the cathode does not contact the nozzle wall (for example, the gap between the cathode and the inner wall of the nozzle is fixed at 0.5mm), and the diameter of the metal rod is slightly smaller than the nozzle. The inner diameter of the nozzle is 2mm, and the gap between the cathode and the nozzle is 0.5mm to avoid uneven discharge and ensure the laminar flow characteristics of the jet. The distance between the nozzle and the substrate is fixed at 2mm, which is the optimal activation distance. The gas system consists of a working gas and a reactive gas. The working gas is argon at a flow rate of 15 SLM (standard liters per minute), and the reactive gas is oxygen at a flow rate of 40 SCCM (standard cubic centimeters per minute). Oxygen excites the surface to generate reactive oxygen atoms, enhancing surface hydroxylation.

[0055] The parameters of the DC power supply are 150V and 1A; The base fabric is placed on the substrate, and the working gas is mixed with the reaction gas and injected into the nozzle. A DC power supply of 150V and 1A is applied to ignite the plasma. A blue glow discharge appears at the tip of the nozzle, and the generated plasma jet scans the entire substrate area at a constant scanning rate of 4s / cm², completing the surface activation of the base fabric and depositing a nano-metal oxide layer on the upper surface of the base fabric.

[0056] Step S303: evaporation at room temperature and pressure.

[0057] For a superhydrophobic surface, the surface energy should be as low as possible. Reagents with perfluoroalkyl chains can reduce the surface energy.

[0058] The substrate was placed in a sealed container and suspended to avoid contact with the container walls. A fluorosilane surface modifier, FAS-17 (chemical name: 1H,1H,2H,2H-perfluorodecyltriethoxysilane), was then injected into the container. The volume ratio of the fluorosilane surface modifier to the sealed container was 0.012% (i.e., 120µL of fluorosilane surface modifier was used per 1L of the sealed container). The fluorosilane surfactant concentration was 97%, and the substrate was not in direct contact with the substrate. The container was then allowed to stand at room temperature for one hour to isolate it from the outside air and reach saturated vapor pressure. This resulted in a colorless, low-surface-energy, superhydrophobic coating on the substrate, forming a composite substrate.

[0059] Step S4, hot pressing and shaping: After the composite base fabric is preheated by infrared to 100~120℃, the folding line is pre-pressed by a CNC crease pressing device with a pre-pressing pressure of 0.5~1.2MPa. It is then shaped by high-temperature hot air in the temperature range of 160~180℃ and the duration is 30~60s, so that the PA6 molecular chains are oriented and form a permanent crease memory.

[0060] The numerically controlled crease pressing device may adopt the load crease device disclosed in Chinese patent publication number CN113737358A.

[0061] This solution utilizes a three-step shaping process: infrared preheating and softening, which uniformly heats the composite fabric, eliminates internal fiber stress, and enhances subsequent plastic deformation. Mechanical shaping with pressure creates precise fold lines on the fabric surface, providing a physical guide for molecular chain rearrangement. Hot air molecular chain orientation: The high temperature causes the polyamide 6 molecular chains to align along the crease, forming a stable orientation structure and irreversibly fixing the crease shape.

[0062] An umbrella, the base fabric of which adopts the super-hydrophobic coating described above, or the base fabric of which adopts the preparation method described above.

[0063] This composite base fabric has super-hydrophobic, self-cleaning and automatic folding and storage functions, and is suitable for high-end rain gear.

[0064] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a super-hydrophobic coating, characterized in that, The following steps are involved: Step S1, base fabric pretreatment: Wash and dry the base fabric to remove surface contaminants; Step S2, using an atmospheric pressure plasma jet device to perform surface activation on the base fabric: The atmospheric pressure plasma jet device includes a cathode, a nozzle, a substrate, a gas system, and a DC power supply. The cathode is made of tungsten metal. The gas system consists of a working gas and a reaction gas, wherein the working gas is argon and the reaction gas is oxygen. The base fabric is placed on the substrate, and the working gas and the reaction gas are mixed and injected into the nozzle. Applying a DC power supply to ignite the plasma, a blue glow discharge appears at the nozzle tip, and the generated plasma jet scans the entire substrate area at a constant scanning rate, completing the surface activation of the base fabric and depositing a nano-metal oxide layer on the upper surface of the base fabric; Step S3, evaporation at room temperature and pressure: The base fabric is placed in a sealed container and fixed in suspension; the fluorine-containing silane surface modifier FAS-17 is injected into the sealed container; and the sealed container is allowed to stand at room temperature to isolate the sealed container from the outside air and reach saturated vapor pressure, thereby obtaining a colorless, low-surface-energy super-hydrophobic coating on the surface of the base fabric to form a composite base fabric.

2. a preparation method of super hydrophobic coating according to claim 1, is characterized in that, In step S1, the base fabric is ultrasonically cleaned in acetone, isopropyl alcohol, and deionized water for 4 to 6 minutes each; and then dried in an oven at 80° C. for 30 minutes.

3. A method for preparing a super-hydrophobic coating according to claim 1, wherein In step S2, the nozzle is made of stainless steel, and a metal rod with a diameter of 1 mm and a length of 175 mm is placed at the center of a stainless steel nozzle with a diameter of 2 mm; the inner diameter of the nozzle is 2 mm, and the gap between the cathode and the nozzle is 0.5 mm; the distance between the nozzle and the substrate is fixed at 2 mm; the parameters of the DC power supply are 150 V and 1 A; the working gas is argon with a flow rate of 15 SLM; and the reaction gas is oxygen with a flow rate of 40 SCCM.

4. A method for preparing a super-hydrophobic coating according to claim 3, characterized in that, In step S3, the volume ratio of the fluorine-containing silane surface modifier to the sealed container is 0.012%.

5. A method for preparing a shape memory composite base fabric, characterized in that: Includes the following methods: Step S1, base fabric weaving: The warp yarn is made of polyamide 6 filament; the weft yarn is made of polypropylene monofilament and polyamide 6 low-elastic yarn mixed in a ratio of 1: (2-4); The base fabric adopts double-layer jacquard weaving, including surface layer and bottom layer; the surface layer is plain weave structure, with a warp density of 380 to 450 yarns per inch and a weft density of 300 to 380 yarns per inch; the bottom layer is honeycomb grid structure with a grid aperture of 0.5 to 1.0 mm; Step S2, calendering treatment: the hydrostatic pressure resistance value of the base fabric after calendering is ≥350mm water column; Step S3, compounding the hydrophobic coating, comprises: Step S301: pre-treatment of base fabric: Wash and dry the base fabric to remove surface contaminants; Step S302: Activate the surface of the base fabric using an atmospheric pressure plasma jet device. The atmospheric pressure plasma jet device includes a cathode, a nozzle, a substrate, a gas system, and a DC power supply. The cathode is made of tungsten metal; the gas system consists of a working gas and a reactive gas, wherein the working gas is argon and the reactive gas is oxygen. The substrate is placed on the substrate, and the working gas and reactive gas are mixed and injected into the nozzle. A DC power supply is applied to ignite the plasma, and a blue glow discharge appears at the tip of the nozzle. The generated plasma jet scans the entire substrate area at a constant scanning rate, completing the surface activation of the substrate and depositing a nano-metal oxide layer on the upper surface of the substrate. Step S303: evaporation at room temperature and pressure: The base fabric is placed in a sealed container and fixed in suspension; a fluorinated silane surface modifier FAS-17 is injected into the sealed container; and the container is allowed to stand at room temperature to isolate the sealed container from the outside air and reach saturated vapor pressure, thereby forming a colorless, low-surface-energy super-hydrophobic coating on the surface of the base fabric, thereby forming a composite base fabric; Step S4, hot pressing and shaping: After the composite base fabric is preheated by infrared to 100~120℃, the folding line is pre-pressed by a CNC crease pressing device with a pre-pressing pressure of 0.5~1.2MPa. It is then shaped by high-temperature hot air in the temperature range of 160~180℃ and the duration is 30~60s to form a permanent crease memory.

6. A method for preparing a super-hydrophobic coating according to claim 5, characterized in that, Step S1, polyamide 6 filament, specification range of 40 to 80 denier, number of monofilaments 48 to 144; Specifications of polypropylene monofilament: 20 to 60 denier, number of monofilament is 1; specifications of polyamide 6 low-elastic yarn: 30 to 70 denier, number of monofilament is 36 to 96.

7. A method for preparing a super-hydrophobic coating according to claim 5, characterized in that, Step S2, during the calendering treatment, the temperature is 150-170°C; the pressure is 13-17 MPa; the speed is 16-20 m / min; and the cooling method is air cooling.

8. A method for preparing a super-hydrophobic coating according to claim 5, characterized in that, In step S301, the base fabric is ultrasonically cleaned in acetone, isopropyl alcohol, and deionized water for 4 to 6 minutes each; and then dried in an oven at 80°C for 30 minutes; In step S302, the nozzle is made of stainless steel, and a metal rod with a diameter of 1 mm and a length of 175 mm is placed at the center of a stainless steel nozzle with a diameter of 2 mm. The inner diameter of the nozzle is 2 mm, and the gap between the cathode and the nozzle is 0.5 mm. The distance between the nozzle and the substrate is fixed at 2 mm. The parameters of the DC power supply are 150 V and 1 A. The working gas is argon at a flow rate of 15 SLM; the reaction gas is oxygen at a flow rate of 40 SCCM. In step S303 , the volume ratio of the fluorine-containing silane surface modifier to the sealed container is 0.012%.

9. An umbrella, characterized in that: The base fabric adopts the super-hydrophobic coating according to any one of claims 1 to 4, or the base fabric adopts the preparation method according to any one of claims 5 to 8.

Citation Information

Patent Citations

  • High cover factor double-layer jacquard color-woven fabric and its weaving process

    CN101046025A

  • Jacquard weaved double-layer perforated fabric and weaving method thereof

    CN106884247A

  • Production process of jacquard fabric with petit point effect

    CN110144663A

  • Preparation process of easy-to-fold umbrella cloth

    CN113737358A

  • Manufacturing method of double-layer knitted fabric with 3D honeycomb effect and fabric

    CN117005096A